Effects of postmastectomy radiotherapy on survival in different age groups for patients with T3N0M0 breast cancer - Meng-Ting He; Xun-Xi Lu; Zong-Chao Gou (Breast, 2021)
Background: Postmastectomy radiotherapy (PMRT), as an important regional treatment, improves the survival rate of patients with T3N0M0 breast cancers. However, the therapeutic effect of PMRT on T3N0M0 patients in different age groups is unclear. Methods: Using Surveillance, Epidemiology, and End Results database, we identified 4840 T3N0M0 patients between 2000 and 2015. The primary and secondary outcomes were overall survival (OS) and breast cancer-specific survival (BCSS). Survival outcomes were compared using Kaplan-Meier survival test, COX regression analysis, propensity score matching and forest plot, which present the relationship between age and PMRT. Results: Survival analysis demonstrated that for young patients (aged 18–45 and 46–55), there was no significant difference in OS between with and without PMRT. However, for patients older than 65 years, PMRT could significantly improve survival time (P < 0.001). Multivariate Cox analysis of OS showed older patients with PMRT had a lower hazard ratio (HR) than those without PMRT (aged 56–65: HR = 0.67, P = 0.014; aged >65: HR = 0.60, P < 0.001), and little benefit for young patients. The consistent results were also observed in 1:1 matched cohort. Subgroup analysis revealed the survival HRs of with versus without PMRT for patients older than 65 years were significant in most subgroups. Conclusion: The effect of PMRT in T3N0M0 patients is related to the age. PMRT is associated with improved survival in older patients with T3N0M0 breast cancer, especially those older than 65 years. While the benefit of PMRT is limited in T3N0M0 patients of young age. The observation suggests the importance of age for T3N0M0 patients when individualized treatment is made.